Sensorineural Hearing Loss After Balloon Eustachian Tube Dilatation - Todt, Ingo; Oppel, Felix; Sudhoff, Holger (Frontiers in Surgery, 2021)
Objective: Eustachian tube function is of central importance for the ventilation of the middle ear. A dysfunction can be associated with chronic otitis media, and cholesteatoma. Balloon Eustachian tube dilatation (BET) is a treatment option used to solve eustachian tube dysfunction. Although BET is widely performed, little is known about the occurrence rate of the complications associated with BET. The aim of the present study was to observe the rate of sensorineural hearing loss (SNHL) after BET. Methods: We retrospectively evaluated in a chart review 1,547 patients and 2,614 procedures of BET performed in a single center between 2015 and 2019 using the Spiggle and Theis, Overath, Germany eustachian tube dilatation system. Results: We observed seven cases of SNHL after BET. In two cases, the SNHL persisted, and in five cases, the SNHL was transient. In two cases of SNHL, a simultaneous tympanoplasty was performed. The overall rate of SNHL per procedure is 0.3%. The rate of permanent SNHL is 0.08%. Conclusion: BET has a low rate of SNHL. Rapid middle ear pressure changes are assumed to cause BET-related hearing loss.